2013
DOI: 10.3109/19396368.2012.743197
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative status in granulosa cells of infertile women undergoing IVF

Abstract: Studies on elevated reactive oxygen species (ROS) levels in granulosa cells (GC) and its subsequent effect on fertilization are limited. Oxidative stress (OS) mediated alterations in GC of infertile women undergoing in vitro fertilization (IVF) and embryo transfer (ET) was investigated. GC were obtained from 28 women with endometriosis (Group A), 26 women with polycystic ovary syndrome (PCOS) (Group B), and 32 women with tubal factor infertility (Group C). GC characteristics including cell count, viability, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 29 publications
3
38
0
2
Order By: Relevance
“…This imbalance can lead to many pathological effects including lipid peroxidation, DNA fragmentation, and ultimately mitochondrial alterations, apoptosis, and fetal growth arrest [30]. ROS is involved in the pathophysiology of a number of female reproductive tract disorders such as endometriosis, polycystic ovary syndrome, preeclampsia maternal diabetes [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…This imbalance can lead to many pathological effects including lipid peroxidation, DNA fragmentation, and ultimately mitochondrial alterations, apoptosis, and fetal growth arrest [30]. ROS is involved in the pathophysiology of a number of female reproductive tract disorders such as endometriosis, polycystic ovary syndrome, preeclampsia maternal diabetes [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In the follicular microenvironment, besides granulosa cells, leukocytes and macrophages can also be found and all these cell types are able to produce ROS [41]. Furthermore, the expression of antioxidant enzymes in cells that produce steroids (granulosa, thecal and luteal cells) was also reported [42,43]. This suggests that the oocyte is physiologically exposed to oxidative stress and to antioxidant activity both present in the FF [44].…”
Section: Discussionmentioning
confidence: 99%
“…Kossowska-Tomaszczuk et al [41] isolated GCs from aspirated follicular fluid of infertile patients based on FSHR; Varras et al [77] collected GCs from cumulus-oocyte complex during oocyte retrieval from fertile patients; and Mattioli et al [47] scraped GCs from internal face of the follicle wall obtained from prepubertal pigs. First variable which can affect differences in stem cell markers is fertility since it was found that the cause of female infertility can drastically affect the GCs viability [34]; therefore this factor should always be taken into account when discussing the stem cell characteristics of GCs. Secondly, expression of genes varies between species and projection (e.g.…”
Section: Expression Of Stem Cell Markers In Granulosa Cells From Follmentioning
confidence: 99%